Developing Prezi Learning Media with Interactive Content to Learn Descriptive Text for SMPN 1 Karangan in Trenggalek - Fahrizal Fahrizal (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2021)
Media has an important role in conveying something, especially in learning activities. Further, learning media is anything that can be used to deliver learning material, so that it can stimulate students' attention, interests, thoughts, and feelings in learning activities to achieve learning goals. The objective of the research is the development of Prezi learning media. The design of this research is Research and Development (R&D). Latief in Basuki (2017:13) as one research design aimed at developing educational products, like curriculum, syllabus, textbooks, instructional media, etc. Also, this research using quasi-experimental to gather the data. The seventh grade 2019/2020 academic year consists of 32 students of 7. The instruments use in this research are questionnaires. The data collected by questionnaire is analyzed quantitatively way. The product is developed based on students’ needs, studying the theory of R&D, studying the theory of descriptive text, media learning, and Prezi. The product is developed in five steps development. The result of the need analysis score is the respondent agrees that Prezi media learning needs to be a learning media. Then, the result of field-testing is the respondent agrees that the product of this research was very good and feasible to use as media in learning descriptive text. The result of the questionnaire during collecting the data; the mean score of experimental groups before treatment (Pretest) is 67.5. Meanwhile, the mean score of the experimental group after treatment (Posttest) is 78.06. The explanation above means that the product of this research, developing Prezi media learning, is an effective learning media for junior high school students to introduce descriptive text material.